Implementing Deep Learning to Enhance Critical Thinking Skills in Early Childhood: A Qualitative Study at Aisyiyah Bustanul Athfal 26 Kindergarten, Malang - Baria Ulfah; M. Syahri; Dyah Worowirasti Ekowati (Journal of General Education and Humanities, 2026)
This study addresses the persistence of one-way instructional practices in early childhood education that limit the development of children’s critical thinking skills. It aims to describe the implementation of a deep learning pedagogical approach and its impact on critical thinking among children aged 5-6 years at Aisyiyah Bustanul Athfal 26 Kindergarten, Malang. A descriptive qualitative method was employed, with data collected through observations, semi-structured interviews, and documentation involving teachers, children, and the school principal. Data were analyzed using an interactive qualitative analysis technique, including data reduction, data display, and conclusion drawing. The findings indicate that deep learning is implemented through meaningful, mindful, and joyful learning experiences, where teachers act as facilitators and children actively engage in exploration and play-based activities. The results show a noticeable improvement in children’s critical thinking, reflected in increased curiosity, a willingness to ask questions, the ability to provide simple, logical reasons, and growing independence in solving everyday problems. These outcomes suggest a positive shift in children’s thinking from passive reception to more reflective engagement. However, the study does not claim absolute effectiveness, as the results are context-specific and influenced by teacher readiness and learning environment. Overall, the deep learning approach (as a pedagogical model, not an AI-based approach) provides opportunities for children to construct knowledge through meaningful experiences.